TAXATION OF TRANSACTIONS IN THE RUSSIAN GOLD MARKET - Nataliya V. Zolotova; Vitaly T. Borisovich (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The results of the analysis of taxation operations in the Russian gold market have been presented. Detailed specifications on the types of transactions, taxes and duties on the precious metals market have been enumerated. Economic report analysis of one of the leading gold mining companies of Russia have been conducted, the issues of taxation have been determined and the ways of resolving them have been proposed. The influence of the tax burden on the investment attractiveness of the Russian gold market has been shown. The issues of the gold mining industry and the banking sector are considered. The main tasks of improving the system of subsoil user payments to ensure an equitable distribution between the state and subsoil users of revenues from the use of mineral resources are noted.